Mediation of Online Learning Performance on The Effect ‎of‎Metacognition on Mathematics Achievement - Castillo, Romer C. (International Journal of Basic and Applied Sciences, 2025)
The purpose of the study is to establish the relationships among metacognition, online learning performance, and mathematics achievement. ‎More particularly, it aims to determine the effects of metacognitive knowledge and metacognitive regulation on mathematics achievement ‎and the mediating role of online learning performance on these effects. The study employs linear regression and the Sobel test for its mediation ‎analysis using the data gathered from 311 students who answered the survey questionnaire. Results showed that most students have high ‎levels of metacognitive knowledge and metacognitive regulation, with satisfactory online learning performance, and attain mathematical ‎proficiency. Both metacognitive knowledge and metacognitive regulation have significant positive effects on mathematics achievement and ‎on online learning performance. However, online learning performance does not significantly mediate the effect of each of the metacognitive ‎knowledge and metacognitive regulation on mathematics achievement. Therefore, mathematics educators and institutions should exert efforts ‎and develop strategies to enhance the students’ metacognition for better mathematics achievement and online learning performance. They ‎may also either enhance their online learning platforms or revert to traditional classroom learning settings for mathematics courses, but further studies on this matter are suggested before deciding‎.
Keywords: Mathematics Achievement; Metacognition; Metacognitive Knowledge; Metacognitive Regulation; Online Learning Performance